Development and Validation of Spectrophotometric and RP-HPLC Method for Estimation of Olmesartan Medoxomil in Tablet Dosage Form - Prabhat Jain,; Anurekha Jain,; Deepika Maliwal,; Vaibhav Jain, (International Journal of Pharma and Bio Sciences, 2010)
Two simple and sensitive spectrophotometric and RP-HPLC methods are described for the determination of Olmesartan Medoxomil. The first method Spectrophotometry was based on the standard curve. Olmesartan Medoxomil exhibits λmax at 258 nm. Quantitative estimation of Olmesartan Medoxomil was carried out the standard calibration curve at 258 nm. The second method, high-performance liquid chromatographic method was developed for the determination of Olmesartan Medoxomil using Acetonitrile: Methanol (50:50, v/v) and pH adjust 4.0 with glacial acetic acid as the mobile phase and measuring the response at λmax 256 nm. The analysis was performed on a Lichrocart C18 (250 X 4.0 mm), 5-µm column. The method was found to be accurate, with linearity ranging from 2 to24 for spectrophotometry and 5 to30 for HPLC with a correlation coefficient (r2) 0.9994 and 0.9996 respectively. Precision mean % assay was found to be 99.09 for spectrophotometry and 99.53 for HPLC, The mean % recovery was found to be 99.5 -107.01 for spectrophotometry and 100.6-106.9 for HPLC.